The Influence of Playing Methods on Learning Outcomes of Physical Education at SDN Beusi 1 Ligung District Majalengka District - Firmanysah, Ferdy; Rustandi, Endi; Prabowo, Indra (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
The goal of this study was to ascertain how the play approach affected the assessed students' learning outcomes in SD Negeri 1's Ligung sub-district and Majalengka regency. Pre-experiment research is this kind of study. The one-shot case study design method was employed in this investigation. Ligung Majalengka regency's SD Negeri 1 subdistrict serves as the study's population. 30 SD Negeri Beusi 1 grade IV students made up the study's sample. The Game Performance Assessment Instrument (GPAI) is the test's instrument of choice. In order to determine the average value of the posttest results following treatment with the same sample, the data analysis technique employs the paired-t test with the aid of the SPSS 25 application. Test the normalcy first, then perform the paired t test. The average student experienced an increase, and there was a significant influence following treatment using the play method, which led to the conclusion that the play method has an impact on the assessee's learning outcomes in SD Negeri Beusi 1 sub-district's ligung majalengka district